Aspects of Psychological and Pedagogical Adaptation of Students to the Educational Process - Khayrulloh, Tuichiev (European Journal of Life Safety and Stability (2660-9630), 2021)
Currently, while improving the education system, much attention is paid to the training of mature, competent, strong-willed, self-sacrificing and initiative personnel in all aspects. The main tasks of modern education today are independent critical thinking of teachers, independent search and retrieval of information, and the development of a culture of intellectual work.